A Clinical Trial of Kampo Formulae for the Treatment of Symptoms of Yusho, a Poisoning Caused by Dioxins and Related Organochlorine Compounds. (9th January 2011) - Uchi, Hiroshi; Tokunaga, Shoji; Mitoma, Chikage; Shibata, Satoko; Hamada, Naoki; Nakanishi, Yoichi; Kajiwara, Junboku; Yoshimura, Takesumi; Furue, Masutaka
Abstract : The objective of this study was to evaluate the effectiveness of traditional herbal medicines (Kampo) on the symptoms of Yusho. Yusho is a mass food poisoning that was caused by ingestion of rice oil contaminated with dioxins and related organochlorines in 1968. Patients with Yusho suffer from skin symptoms (acneform eruptions, liability to suppuration and pigmentation), respiratory symptoms (cough and expectoration of sputum), neurological symptoms (numbness and paresthesia of extremities), arthralgia and general fatigue, and no effective treatment has yet been developed. In this clinical trial, four Kampo formulae (Bakumondo-to, Keigai-rengyo-to, Gosha-jinki-gan and Hochu-ekki-to) were administered to four representative Yusho symptoms (respiratory, skin, neurological symptoms and general fatigue), respectively. Twenty-seven Yusho patients were enrolled and two formulae were administered to each patient for half-a-year each. The effectiveness of Kampo formulae was estimated by changes in the intensity of symptoms measured by a visual analogue scale (VAS) of 100 mm recorded at baseline and after administration of each formula. The influence of Kampo formulae on patients' quality of life (QOL) was also assessed by the SF-36 (NBS). Twenty-five patients completed the treatment. Bakumondo-to significantly improved respiratory symptoms as well as patients' QOL in the context of vitality, compared with other formulae. In contrast, Hochu-ekki-to impaired patients' QOL in the context of physical functioning and vitality, compared with other formulae. This study demonstrated for the first time that a Kampo formula Bakumondo-to is useful for treating respiratory symptoms caused by dioxins.